2016
DOI: 10.1088/0963-0252/25/6/06lt03
|View full text |Cite
|
Sign up to set email alerts
|

Pressure broadening of atomic oxygen two-photon absorption laser induced fluorescence

Abstract: Atomic oxygen, considered to be a determining reactant in plasma applications at ambient pressure, is routinely detected by two-photon absorption laser induced fluorescence (TALIF).Here, pressure broadening of the (2p 4 3 P 2 → 3p 3 P J=0,1,2 ) two-photon transition in oxygen atoms was investigated using a high-resolution TALIF technique in normal and Doppler-free configurations. The pressure broadening coefficients determined were O2 γ = 0.40 ± 0.08 cm −1 /bar for oxygen molecules and He γ = 0.46 ± 0.03 cm −1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…Finally, the pressure broadening is determined as Δ σ L = 0.37 cm –1 from an average of several automated fits to the data using the previously specified values for Δ σ D and Δ σ I . This value is in reasonable agreement with Δ σ L = (0.46 ± 0.03) cm –1 for He measured by Marinov et al 59 in the ‘COST Reference Microplasma Jet’ using Doppler-free TALIF, albeit for a different optical transition.…”
Section: Methodssupporting
confidence: 91%
“…Finally, the pressure broadening is determined as Δ σ L = 0.37 cm –1 from an average of several automated fits to the data using the previously specified values for Δ σ D and Δ σ I . This value is in reasonable agreement with Δ σ L = (0.46 ± 0.03) cm –1 for He measured by Marinov et al 59 in the ‘COST Reference Microplasma Jet’ using Doppler-free TALIF, albeit for a different optical transition.…”
Section: Methodssupporting
confidence: 91%
“…Apart from a discrepancy at 3 μs in the broadening of the absorption line which cause is unclear, both have the same temporal dependence. Marinov et al recently reported the pressure broadening of atomic oxygen TaLIF in He [65]. They showed that non-quenching collisions are responsible for the observed pressure broadening.…”
Section: H Densitymentioning
confidence: 97%
“…At our experimental conditions, Doppler broadening is typically one order of magnitude larger than pressure broadening and similar to the laser broadening. Hence a further improvement on the resolvability of the rotational lines can be achieved by measuring Doppler-free excitation spectra, although this is experimentally challenging [5,26].…”
Section: Spectral Profile Of Fluorescencementioning
confidence: 99%